Swot Analysis of Supporting Marketing Strategy Cooperative Existence in Correctional Institution - Riyanto Riyanto (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
The life of prisoners in the Penitentiary is very limited in meeting their needs and experiencing conditions of revocation of the right to freedom of movement limited by the prison walls. On the other hand, there is access to fulfillment of needs through visitors' luggage, and there are also illegal shanties where inmates who sell inside the selling block can threaten the existence of cooperatives inside prisons, which is considered more expensive than items outside of prison. This study aims to determine the marketing strategies used by organizations in prisons effectively and efficiently to maintain their existence. In this study, the authors used a descriptive qualitative research method with data collection methods through interviews, observation, documentation, and literature studies. The marketing strategy of Purwokerto Penitentiary Cooperative based on the results of the SWOT analysis shows the need for regulations to regulate visitors with their cargo and need to collaborate with investors, producers, distributors, and managers of cooperatives.